Anesthesia Management in An Adult Patient with Desbuquois Syndrome - Tümer, Murat; Kökten, Hazar; Ankay Yılbaş, Aysun; Sarıcaoğlu, Fatma (Acta Medica, 2022)
Desbuquois syndrome (DS) is a rare disease that can be accompanied by a difficult airway. In the literature, there are usually case reports about the mortal forms in childhood. We wanted to share our anesthesia experience in an adult patient with DS who underwent orthopedic surgery. We used videolaryngoscopy for intubation with coronavirus precautions. Adult patients with DS can be managed safely with adequate difficult airway preparation.